Pneumothorax following ERCP: Report of Two Cases with Different Pathophysiology. (24th June 2013) - Neofytou, Kyriakos; Petrou, Athanasios; Savva, Constantinos; Petrides, Christos; Andreou, Charalampos; Felekouras, Evangelos; Loizou, Sakis
Abstract : In the last thirty years, the widespread use of endoscopic retrograde cholangiopancreatography (ERCP) has radically changed the management of patients with diseases of the extrahepatic biliary tract and pancreas. Pneumothorax is a rare complication of ERCP. We report two cases of pneumothorax following elective ERCP for ductal stone clearance. The first patient was a 45-year-old female, who developed respiratory distress, abdominal pain, and profoundly abdominal distention immediately after the procedure. Imaging studies revealed the presence of a right-side pneumothorax, pneumomediastinum, pneumoperitoneum, and pneumoretroperitoneum. The second patient was a 94-year-old female, who developed tension pneumothorax with clinical signs of shock during the procedure. Imaging studies revealed the presence of a right-side pneumothorax without free air in the mediastinum and retroperitoneal space. The imaging findings suggest that the occurrence of this rare complication in our patients was caused by entirely different pathophysiological mechanisms. Both patients were successfully treated with chest tube insertion, and no further intervention was required. Clinicians should be aware of this serious complication because delayed diagnosis may involve significant morbidity and mortality risks.